An integrated mindfulness and acceptance-based program for young elite female basketball players: Exploratory study of how it works and for whom it works best - Goisbault, M.; Lienhart, N.; Martinent, G.; Doron, J. (Psychology of Sport and Exercise, 2022)
In order to better understand how an integrated mindfulness and acceptance-based intervention works and for whom it works best, study objectives were to examine (i) the trajectories of mindfulness skills and performance-related outcomes during the intervention, and athletes` perceptions of the impact of the intervention; and (ii) the potential moderating effects of personality characteristics on changes in targeted variables associated with the intervention. The sample consisted of 40 young elite female basketball players (M = 16.33, SD = 0.75 years) from three incoming groups at the French Federal Basketball Center over a 3-year period. All players participated in a 15-week Mindfulness BasketBall Integrated program. They completed online questionnaires measuring personality traits 10 months before the intervention, as well as pre-, mid- and post-intervention measurements of mindfulness skills, intensity and directional interpretation of stress, and performance satisfaction. They also participated in semi-structured social validation interviews conducted one month after the intervention. The results of the multilevel growth curve (MGCA) and thematic analyses revealed how the mindfulness skills and performance-related outcomes evolved over the course of the intervention and how these changes were perceived by the athletes. Specifically, the MGCA showed significant linear increases in acceptance, positive stress direction, and performance satisfaction. The complementary social validation data indicated perceived improvements in mindfulness skills and performance. The MGCA also showed that baseline personality traits moderated the effects of the program on acceptance and experience of stress. These findings may be used to inform the design of more effective integrated mindfulness and acceptance-based interventions.